A new nonisolated soft switched DC‐DC bidirectional converter with high conversion ratio and low voltage stress on the switches. (18th October 2020) - Vesali, Mahmood; Delshad, Majid; Adib, Ehsan; Amini, Mohammad Reza
Abstract: Background: With the increase in demand for generating power using photovoltaic systems (PVs), bidirectional converters for energy storage in these systems have become a major challenge. Reducing the losses and the operation complexity are the main aims in designing the bidirectional converters. Purpose: This paper explores how the voltage gain of bidirectional converters improves, increasing in the boost mode and decreasing in the buck mode. It also describes how the efficiency is increased by providing soft switching conditions for all semiconductor elements. Design/Method: In this paper, a new ZVS bidirectional DC‐DC converter with high conversion ratio is proposed. In the proposed converter to achieve soft switching condition for each direction, a separate auxiliary switch is used, which provides ZVS condition for the main switches, therefore, the converter efficiency is increased. Additional auxiliary switches are switched as the complements with the main switches, therefore, the operation of the converter is simple and the complex control circuit is not required. To improve voltage gain, coupled inductors and series capacitors in the power path have been used. Results: The proposed converter has low voltage stresses in both directions, so, low‐voltage power MOSFETs with low RDS(on) can be used in the converter. Also, due to the creation of soft switching condition on the switches, the proposed converter has low EMI noise compared to the conventional one. A 100 W prototype of the proposed converter is implemented, and the experimental results are presented to confirm the theoretical analysis. The proposed converter under full load has a 96.5% efficiency and EMI noise has been obtained by a decrease of 11dBμv in comparison with the conventional one. Conclusions: This paper helps the reader to learn how to the increase voltage gain and efficiency in bidirectional converters. It also presents new technique to provide soft switching condition and improving voltage gain with minimum elements in non‐isolated bidirectional converters. Abstract : A new zero voltage switching (ZVS) bidirectional DC‐DC converter with high conversion ratio is proposed. The proposed converter has low voltage stresses in both directions. Also, due to the creation of soft switching condition on the switches, the proposed converter has low electromagnetic interference (EMI) noise compared to the conventional one. The proposed converter under full load has a 96.5% efficiency.